Perceived Acceptance of Mobile Advertising in Maldives - Mohamed, Auzam (2016)
Advertising media has become largely very competitive over the years. One of the reasons it has become so competitive is because of the rapid rise in technology that evolved in the recent years starting from internet, then mobile phones and later smart phones. More and more marketers have become aware of the mobile advertisements in which they have become interested in venturing into the market. One of the most prominent reason that this media has struck the minds of marketers is that mobile devices are one of the personal things consumers are attached compared to other media’s such as TV, and Internet. Hence new world of communication of interaction and communication has emerged over the years with the rise if mobile technology. This research seeks to understand mobile advertising perspective from Maldives which is a small country. The researcher has extensively researched about the area through the existing literature reviews published in journal articles. The researcher has developed the frame work from an existing an existing framework derived from a journal article and made slight changes to the model. For the research, researcher has incorporated three different factors as contributing to increase in behavioural intention to use mobile advertising. They are attitude, perceived behavioural control and subjective norms. To carry out the research and test the hypothesis, questionnaires and developed and developed and circulated to collect the data. Finally these data’s are analysed and conclusions are laid and further recommendations are explored in the research.